SMARTPHONE-BASED ANALYSIS OF CLOTH MASKS PORES SIZE - Meri Hamdini; Yuant Tiandho (Jurnal Neutrino: Jurnal Fisika dan Aplikasinya)
Until now, the world is still facing the spread of the SARS-CoV-2 virus that causes COVID-19. This virus can be transmitted from human to human through droplets, so more vigilance is needed to avoid contracting this virus. One of the steps to minimize the spread of Covid-19 is to wear a face mask. In practice, most people prefer to use cloth masks than disposable medical masks because they are cheap and reusable. Cloth pore size influences the filtering ability of the cloth masks. Therefore, it is necessary to analyze the efficiencies of the cloth masks. In this study, we developed a method for measuring the pores of a cloth mask using a smartphone. In this study, we developed a method for measuring the pores of a cloth mask using a smartphone. We used the camera zoom application on a smartphone and analyzed the image using image processing software, ImageJ. We appliedHuang's algorithm to adjust the image binarization threshold then calculated the Feret diameter as the pore size of the mask. According to the analysis, the pore size ranged from 0.133 to 0.232 mm, and the efficiency ranged from 77.4 to 82.6%.